The use of midwife-led primary antenatal care by obese women in The Netherlands: An explorative cohort study. (June 2017) - Daemers, Darie O.A.; van Limbeek, Evelien B.M.; Budé, Luc M.; Wijnen, Hennie A.A.; Nieuwenhuijze, Marianne J.; de Vries, Raymond G.
Abstract: Objective: to study the effect of body mass index (BMI) on the use of antenatal care by women in midwife-led care. Design: an explorative cohort study. Setting: 11 Dutch midwife-led practices. Participants: a cohort of 4421 women, registered in the Midwifery Case Registration System (VeCaS), who received antenatal care in midwife-led practices in the Netherlands and gave birth between October 2012 and October 2014. Findings: the mean start of initiation of care was at 9.3 (SD 4.6) weeks of pregnancy. Multiple linear regression showed that with an increasing BMI initiation of care was significantly earlier but BMI only predicted 0.2% ( R 2 ) of the variance in initiation of care. The mean number of face-to- face antenatal visits in midwife-led care was 11.8 (SD 3.8) and linear regression showed that with increasing BMI the number of antenatal visits increased. BMI predicted 0.1% of the variance in number of antenatal visits. The mean number of antenatal contacts by phone was 2.2 (SD 2.6). Multiple linear regression showed an increased number of contacts by phone for BMI categories 'underweight' and 'obese class I'. BMI categories predicted 1% of the variance in number of contacts by phone. Key conclusions: BMI was not a relevant predictor of variance in initiation of care and number of antenatal visits. Obese pregnant women in midwife-led practices do not delay or avoid antenatal care. Implications for practice: Taking care of pregnant women with a high BMI does not significantly add to the workload of primary care midwives. Further research is needed to more fully understand the primary maternal health services given to obese women. Highlights: Initiation of care is comparable for obese and normal weight women in primary care. Obese women in primary care have similar numbers of antenatal visits as normal weight women. Obese women do not delay or avoid antenatal primary care.